ANALISIS PENGARUH ANGGARAN PARTISIPATIF TERHADAP BUDGETARY SLACK DENGAN PERTIMBANGAN ETIKA SEBAGAI VARIABEL MODERASI (Studi Kasus pada PT PLN (Persero) Distribusi Jawa Tengah & D.I. Yogyakarta) - Sihombing, Melina Yosephine; Rohman, Abdul (Diponegoro Journal of Accounting, 2017)
Research about the effect of the participatory budgeting to budgetary slack still show inconsistency conflicting results. This study aims to provide empirical evidence about the effect of the participatory budgeting to budgetary slack and the effect of ethical judgement as moderating variable on the relationship between participatory budgeting and budgetary slack.The object of this research is a lower-level managers involved in the budgeting process in PT PLN (Persero) Distribusi Jawa Tengah & D.I. Yogyakarta. Data was collected using a questionnaire research instruments with the total respondents are 40 people. Model analysis used for the first hypothesis is simple linear regression, while the second hypothesis uses moderated regression analysis (MRA).The results indicate that: 1) participatory budgeting significantly positive affects the budgetary slack, showed by the participatory budgeting coefficient of 0.470 with a significance level of 0.022 (<0.05). 2) the value of the coefficient of interaction between participatory budgeting and ethical judgement is - 0.361 with a significance level of 0.030 (<0.05), indicating that the participatory budgeting with ethical judgement significantly negative affecting on the budgetary slack. These results indicates that the ethical judgement is moderating variable.